Functional results after surgical treatment of proximal humeral fractures with phylos plate - Gavrilovski, Andreja; Dimovska Gavrilovska Aleksandra; Trpeski, Simon; Arsovski Oliver; Kostov, Hristijan; Aleksovski Goran; Magdalena Gjorikj Petrushevska; Radmila Mila Mihajlova Ilie (My University, 2021)
Fractures of the proximal end of the humerus are complex. Proper treatment of these fractures requires a good knowledge of the shoulder joint anatomy, mechanics of movement, classification of proximal humeral fracures and various surgical techniques. The aim of our study was to assess the functional result of proximal humeral fractures (Neer III and IV), after open reduction with a locking Phylos plate
Keywords: Proximal humerus fracture; Philos plate